A study on the yield of banaba crude oil extracted by microwave-assisted solvent extraction - Nguyen, Thanh Nga Thi (Animo Repository, 2011)
In t his study, banaba (Lagerstroemia speciosa) crude oil was extracted by microwave-assisted solvent extraction (MASE), one of the so called green technologies. This technology is considered as simple, inexpensive and valuable method which reduces solvent consumption and extraction time, increase in yield and purity. Effects of parameters such as type of solvent (ethanol and ethyl acetate), extraction yimr (2 and 6 minutes) and power with 3 level of power, 30% and 80% of maximum power and solvent to sample ratio, 6"1; 8:1; 10:1 (ml solvent/gr material) on the yield of the crude extract and corosolic acid was examined for all fresh and dried both leaves and fruit. The result shows that the highest yield is 63.95% for fresh leaves at 50% of power, 10:1 (gr/ml) of solvent to sample ratio, 6 minutes and 700C. Whereas, the highest yield of banana fruit si 79.65% at conditions of 50% power, 60% of temperature extraction, 6 minutes and 8:1 (ml ethanol/g of banana fruit).